Natural Color Mangosteen Skin on Canvas Fabric - I Nengah Wirakesuma; I Wayan Mudana (Journal of Social Science, 2024)
The process of creating art on canvas using natural colors from mangosteen peel represents a distinctive artistic endeavor. Mangosteen peel colors possess unique characteristics compared to synthetic ones. Across various dimensions, mangosteen peel colors tend to exhibit natural nuances such as light brown, brownish, reddish-purple, and blue. Painting with mangosteen peel entails a creative process that begins with harvesting the fruit from the garden. Spontaneously, upon splitting the mangosteen fruit into two equal parts, I decided to use the peel to make marks on the canvas. This technique involves spontaneous finger movements, gently, moderately, and sometimes forcefully pressing the canvas. The resulting color effects emerge naturally, correlating with the intensity of finger movements scraping the mangosteen peel on the canvas. The method of creating paintings using mangosteen peel is carried out spontaneously, following stages of art creation: existence, exploration, experimentation, realization, and evaluation. The realization of paintings using mangosteen peel reflects the dynamics of art creation, encompassing elements of visual arts such as light, point, line, space, plane, color, texture, and composition. The artworks produced are titled as expressions of color and line: Expression of Color and Line 1, Expression of Color and Line 2, Expression of Color and Line 3, and so forth. The use of mangosteen peel colors as an alternative medium in the process of creating paintings is driven by the necessity for creativity to achieve artworks of quality, significance, and harmonious value.